Islamic education: a contrastive analysis of Ibn Sina's and Al-Ghazali's views - Ariffin, Adlina (International Islamic University Malaysia, 2011)
Ibn Sina and Al-Ghazali were two great philosophers in the Muslim history. They shared in their ideas, among others, on man, society and education. Their views on these subjects are to some extent different from each other. This paper is devoted to carry out a contrastive analysis of the ideas concerning Islamic education conceptualized by these two scholars, besides referring to their biography, their views on man, morality, society, and man's sources of knowledge; and highlighting their contributions towards Islamic Education.